Active sway control of a gantry crane system using hybrid input shaping and PID control schemes - Latifah, Shabudin (2002)
The idea of this project presents investigations into the development of hybrid input-shaping and PID control schemes for active sway control of a gantry crane system. The main purpose of controlling a gantry crane is transporting the load as fast as possible without causing any excessive sway at the final destination. However, most of the common gantry crane results in a sway motion when payload is suddenly stopped after a fast motion. The failure of controlling crane also might cause accident and may harm people and the surrounding. The application of positive input shaping involves a technique that can reduce the sway by creating a common signal that cancels its own vibration and it also will be used as a feed-forward control which is for controlling to sway angle of the pendulum, while the proportional integral derivative (PID) controller will be used as a feedback control which is for controlling the crane position. The modeling of gantry crane will be used to simulate the system using MATLAB software. The ready-made gantry crane hardware system will be used for real-time experiment. The simulation result will be compare with experiment result. Finally, a comparative assessment of the control techniques is presented and discussed.